Losses do not prevent wide band metamaterial true time delay line applications, GaAs MMIC experimental verification. Issue 11 (19th May 2020) - Herbette, Quentin; Géron, Emmanuel; Dichi, Thierry; Pillet, Grégoire; Lucas, Jerome
Abstract : Losses are often the impairing feature of metamaterial true time delay line devices. In this study, the authors analytically demonstrate that ohmics losses in this kind of structures as well as impedance mismatch depend on the bandwidth. These results allow to consider wide band application for radar systems. It is verified experimentally that metamaterial delay line devices are fitted for wide band delay line applications for they allow low insertion losses, low return loss and tunable delay.